2015
DOI: 10.1038/ijo.2015.129
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to systemic antibacterials and overweight and obesity in Danish schoolchildren: a prevalence study

Abstract: Prenatal exposure to systemic antibacterials is associated with an increased risk of overweight and obesity at school age, and this association varies by birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 53 publications
1
104
3
Order By: Relevance
“…The study by Korpela et al only reported the r -value from linear correlation analysis, but did not report the difference in the z -score of childhood BMI or weight (43). Ultimately, 15 cohort studies involving 445,880 participants were included (1724, 29, 33, 39, 41, 45, 48, 49) (Figure 1). Table 1 showed the characteristics of those 15 cohort studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Korpela et al only reported the r -value from linear correlation analysis, but did not report the difference in the z -score of childhood BMI or weight (43). Ultimately, 15 cohort studies involving 445,880 participants were included (1724, 29, 33, 39, 41, 45, 48, 49) (Figure 1). Table 1 showed the characteristics of those 15 cohort studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Among those 15 studies, 7 studies assessed the relationship between antibiotic exposure and childhood overweight (17, 2224, 33, 39, 41), 7 studies assessed the relationship between antibiotic exposure and childhood obesity (19, 20, 23, 29, 39, 45, 48), 7 studies analyzed the influence of antibiotic exposure on childhood BMI (18, 20, 22, 23, 41, 45, 49), and 2 studies assessed the influence of antibiotic exposure on childhood body weight (21, 22) (Table 1). Twelve studies assessed the relationship between antibiotic exposure during infancy and childhood adiposity, and four studies examined the impact of prenatal antibiotic exposure on childhood adiposity (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, Mueller et al observed in a U.S. cohort that the administration of antibiotics to women in the last two trimesters of pregnancy increased 84% the risk of obesity in children at 7 years old compared to children born to mothers without antibiotics administration at the same period [110]. Also, Mor et al observed similar results in a study performed in Denmark where they showed that prenatal exposure to systemic antibacterials was associated with an increased risk of overweight and obesity at school age, and this association varies by birth weight [111].…”
Section: Epidemiologic Evidencementioning
confidence: 80%
“…Additionally, changes in the microbiome can have particularly compelling effects on tertiary phenotypes, which can affect the well-being of individuals. For example a Danish cohort study of prenatal exposure to antibacterial agents found an increased risk of being obese and overweight later in life in individuals with prenatal exposure to systemic antibacterials (20). Another study, in Canada, showed that the alteration of microbial compositions affects the risk of childhood asthma (21).…”
mentioning
confidence: 99%